178: A New Tool for Improving Access to Developmental Service: The Developmental Passport. Issue 6 (1st June 2014) - Brown, C; Tassone, MC; Lung, E; Huber, J; Maguire, J; Young, E
Abstract: BACKGROUND: Receiving a new developmental diagnosis is challenging for families. The considerable variability in how long it takes families to access services and the proportion of services families receive reflects challenges families face in navigating and accessing the right developmental services. OBJECTIVES: To determine how developmental pediatricians can better support families with a new developmental diagnosis to access the right developmental services. To develop a new tool designed to better support these families through iterative dialogue with both physicians and families. DESIGN/METHODS: We conducted a written survey with developmental pediatricians to elicit concerns on whether families are accessing the right developmental services and to determine the features of an ideal standardized instrument. We used this feedback to develop a new tool, the Developmental Passport, designed to better support parents while accessing services. This tool is inspired by existing passport-type tools already used in healthcare (eg, immunization record), but tailored for the needs of families with a new developmental diagnosis. We conducted a focus group with developmental pediatricians and standardized telephone interviews with caregivers of children with ASD to evaluate the design and utility of the Developmental Passport. We performed a thematic analysis with a semantic approach. RESULTS: Among the 14 developmental pediatricians, half felt that families are usually able to access fewer than 50% of developmental services recommended. The physicians recognized important barriers exist to service access, but indicated families can best identify these. Important barriers identified by 11 caregivers included 1) feeling overwhelmed, both by the diagnosis and their child's symptom severity; 2) difficulty in navigating the developmental service system, which is archaic, time-consuming, and not transparent; 3) financial barriers; 4) lack of communication with publicly-funded developmental service agencies. To provide family-centered care, physicians suggested parents should take ownership of the Developmental Passport. Families supported the Developmental Passport as a simple, effective tool. They made concrete suggestions on the tool's design including best organization of agency presentation and greater focus on accessing financial support. The final tool is a product of an iterative dialogue among the tool's developers, developmental pediatricians, and caregivers. CONCLUSIONS: Families are struggling to access the right services. Both developmental pediatricians and families supported the Developmental Passport in its current form and believe it will be an effective tool to both identify and address these gaps. Further evaluation of the Developmental Passport is required to determine its utility prospectively.